Management of Risk Factors and Associated Causes of Traffic Accidents in Arbil City, Kurdistan, Iraq: A Comprehensive Study - Muhsen Kamal Yasen (New Ideas Concerning Arts and Social Studies Vol. 1, 2025)
Traffic accidents are a contributing factor to any loss of life, property, or services. It happens when a car runs into another car or something else. Certain elements will manifest, resulting in harm and potentially preventable incidents, and reduced by using the right strategies. These losses came from lower production and recovery costs. This study aimed to know management risk factors and associated causes of traffic accidents in Arbil city. This perspective-based study was conducted from January 2008 to December 2023, at Arbil City, Iraq, and all data was calculated by (NIMS). Data was collected and calculated until August 2020 after that some of the cases were not included and collected due to the COVID-19 lockdown. A total of 41669 traffic cases were recorded during 2008-2023. A high prevalence was found in 2023, and 2022 accounted for 4769 (11.44%), and 4613 (11.07%). While low prevalence was seen in 2012, 2015, 2016, 2014, 2018, 2017, 2021, 2020, 2011, and 2010 years accounted 3320 (7.96%), 3119 (7.47%), 3087 (7.40%), 3066 (7.35%), 3008 (7.21%), 2999 (7.19%), 2871 (6.89%), 2485 (5.96%), 2104 (5.04%), 1943 (4.66%), 1295 (3.10%), 1253 (3%), 1023 (2.45%), and 714 (1.71%) respectively. Among all accidents with high prevalence were crashes 33149 (79.66%), 4343 (10.42%), 3182 (7.63%), bicycles 902 (2.16%), and 85 (0.20%). Human conduct is linked to a high rate of traffic accidents leading to injuries and fatalities. Road accidents have become a significant public health hazard. A new technique for reducing the occurrence of this issue is required.